L'allocation de l'aide internationale en éducation dans les États fragiles : réconcilier les objectifs d'efficacité économique et de justice sociale ? - Thomas Poirier (Les éditions de la Maison des sciences de l'Homme, 2014)
Despite 2005, the notion of fragile states was adopted as an operational concept by most of donors. Nearly ten years after, the increasingly intense debates surrounding the post-2015 global education agenda underlines that the issue about fragile states is unresolved. If access to education can be considered as a "public good", the allocation of international aid is justified, since the early 2000s, for its effectiveness. Our empirical analysis focuses on a broad sample of fragile and non-fragile Sub-Saharan countries. Our findings show the emergence of a current contradiction between the inclusive nature of the Education For All goals and the exclusionary nature of the paradigms on which foreign aid is based (effectiveness and results). This situation raises questions about an approach of aid using too consequentialist and whose financial criteria and instruments are clearly not (yet) suited to situations of fragility.